(untitled) (Altre Modernità, 2022)
Metaphor, as cognitive science has pointed out, is much more than just a rhetorical ornament. With it, a certain image of what is communicated is projected and shared. It also serves to structure thought, analyze society or generate certain expectations about reality. Hence, it has seemed to us that its research is necessary in the case of political speeches, since these are the basis of the agenda of daily social interests, from which a certain perspective of a situation is revealed. For this reason, this text aims to study the transmission of the pandemic in the speeches of Spanish politicians in the Congress of Deputies based on the state of alarm decreed by the Government. The analysis of the identifying metaphoric structures of the Covid-19 with a war conflict has been carried out. Its use has been quantified, and related to the speeches of each political leader. Finally, metaphors have been classified into semantic frames or networks that project a certain image of the disease, and also of the action taken by the Government.